2006
DOI: 10.21608/ajs.2006.15365
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Biosorption by Some Bacterial Species Isolated From Drinking Water at Different Sites in Sharqia Governorate

Abstract: The nine most frequent bacterial strains out of 127 were isolated form ten drinking water samples collected from tap water and bottled water in sharqia governorate. The nine isolates were purified and examined for their resistance to increasing concentrations of two heavy metal ions, lead (Pb +2) and iron (Fe +3). Four stains out of the nine isolates encoded I, II, IV, and VIII showed the highest efficiency of both Pb +2 and Fe +3 uptake from nutrient broth media containing 100 ppm of the heavy metal ions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This result agrees with the study of Sag and Kutsal (1995) who reported that the maximum Cu 2+ uptaking by Z. ramigera was between 25-45°C. Furthermore, Arcanobacterium bernardiae and B. amylolikuefaciens achieve their maximum capacity for lead uptaking at 35°C (Aksu et al, 1991;Tohamy et al, 2006;Jackson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This result agrees with the study of Sag and Kutsal (1995) who reported that the maximum Cu 2+ uptaking by Z. ramigera was between 25-45°C. Furthermore, Arcanobacterium bernardiae and B. amylolikuefaciens achieve their maximum capacity for lead uptaking at 35°C (Aksu et al, 1991;Tohamy et al, 2006;Jackson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%